Gender and the Politics of Marijuana. (8th November 2018) - Elder, Laurel; Greene, Steven
Abstract : Objectives: The objectives of this study were to understand why, even though women are more liberal than men on a broad range of issues, when it comes to the increasingly prominent issue of marijuana legalization, the direction of the gender gap is reversed, with women more conservative than men. Methods: Relying on a 2013 Pew survey—unique for the extensiveness of its marijuana questions, including marijuana usage—we explore and attempt to explain the nature of this unusual gender gap. We test several hypotheses rooted in the different life experiences of women and men. Results: We find that women's role as mothers cannot explain this gap, and that mothers are in fact no different from those without children in terms of their support for marijuana policy, as well as their reported use of marijuana. The greater religiosity of women does play a prominent role in the gender gap on marijuana policy, but does not account for the full difference of opinion between women and men. Our findings suggest that men's greater propensity relative to women to use marijuana is a major driver behind the gender gap. Conclusions: Not only are attitudes on marijuana legalization likely to continue to liberalize, but as marijuana legalization and marijuana use become normalized, rather than viewed as immoral and dangerous behavior, the existing gender gap should shrink.